Design and dimensional analysis of interdigital sensor for blood glucose measurement through non-invasive method - Zaharudin, Zarimin; Mohd Mansor, Ahmad Fairuzabadi; Zainuddin, Ahmad Anwar; Adam, Ismail; Khan, Sheroz; Nordin, Anis Nurashikin; Shaikh, Faraz Ahmed; Abdul Kader, Kushsairy; Hamida, Belal Ahmed (Universiti Teknikal Malaysia Melaka, 2020)
Diabetes has shown to be a chronic disease world over, mainly caused due to reduced physical activity and increased obesity. World health organization statistics show diabetes as a leading cause of disability universally. To avoid extreme medical conditions of subjects, regular monitoring of their glucose levels has been suggested. The most common method that has been in use is the pinprick method for glucose monitoring which carries the risk of contamination as well as irritation. One possible approach called noninvasive technique can be adopted to avoid this major concern. This paper presents designing Inter-Digital-Sensor (IDS) for non-invasive sensing of the glucose level. The sensor-based chip once mounted onto the upper arm or pinkie finger of diabetes subject, is able to sense different glucose levels concentration as impedance plots. A set of several simulation results has been obtained using COMSOL for getting optimized dimensions of the sensor digits. This research has presented the generation of an electric field and intensity by using electrode of known length with element spacing varying from 250µm to 600µm developed over 15mm x 20mm sensor area. An IDS of 475µm width spacing with ten (10) digits producing 2.33 pF of capacitance value with impedance resonating at 13 GHz of frequency is reported in this paper.